Knowledge and attitudes towards organ donation among the public in Hospital Universiti Sains Malaysia - Ting, Phang Siok (2020)
Organ donation is the best method of treatment for patients with end-stage organ failure in worldwide. This cross-sectional study is to determine the level of knowledge and attitudes towards organ donation among the public in Hospital Universiti Sains Malaysia. Using convenience sampling, a total of 162 public were recruited into this study. Data were collected from February 2020 until March 2020 using a selfadministered questionnaire. The data was analyzed using SPSS software package version 24.0. Descriptive statistic was used to describe socio demographic characteristics, level of knowledge and attitude towards organ donation. Statistically significant was considered at p value ≤ 0.05. Majority of participants in this study had low level of knowledge (56.8%, n=92) and positive attitude (100%, n=162). There was a significant association between age (p=0.001) and educational level (p=0.001) towards knowledge on organ donation. The study also showed ethnicity (p< 0.001), marital status (p=0.044), employment status (p=0.005) and monthly household income (p=0.025) had significant association towards attitudes on organ donation. There was a fair correlation (r= 0.336) between knowledge and attitudes level towards organ donation. This study findings provide preliminary information to healthcare professional on knowledge and attitude of organ donation and it associated factor influencing knowledge and attitude. Therefore, an effective public awareness campaign according to local culture are needed to raise awareness about organ donation among the public in Malaysia.